Developing a Predictive Model of Antisocial Personality Traits Based on Social Media Addiction Considering the Mediating Role of Psychological Flexibility Among Students - Khodaverdian Dehkordi, Zahra; Mahmoodi, Armin; Ghasemi Pirbalouti, Mohammad (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: The aim of the present study was to develop a predictive model of antisocial personality traits based on social media addiction, considering the mediating role of psychological flexibility among students in Shahrekord. Methods and Materials: The research method was correlational, using structural equation modeling, and the study was applied in terms of its objective. The statistical population included students from Shahrekord Islamic Azad University (7,787), Shahrekord University of Medical Sciences (2,385), and Shahrekord Public University (8,200), amounting to a total of 18,372 individuals. A sample size of 384 participants was determined based on the research objectives, variables, and Cochran’s formula, using a multi-stage cluster sampling method. The research instruments included the Antisocial Behavior Questionnaire by Robinson and O’Leary-Kelly (1998), the Social Media Usage Questionnaire by Rasoolabadi (2015), and the Psychological Flexibility Questionnaire by Dennis and Vander Wal (2010). To test the research model, the two-step approach proposed by Anderson and Gerbing (1988) was employed, and the study’s model was developed accordingly. All analyses were performed using AMOS 24 for structural equation modeling. Descriptive statistics (mean, standard deviation, and frequency) and inferential statistics (correlation matrix, regression, and fit indices) were utilized. Findings: The findings indicated that model validation was assessed using goodness-of-fit indices. Results from the fit indices demonstrated that the measured model exhibited an acceptable level of fit. Conclusion: It can be concluded that the predictive model of antisocial personality traits based on social media addiction, considering the mediating role of psychological flexibility among students in Shahrekord, has a satisfactory fit.